2012
DOI: 10.1093/ndtplus/sfr165
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium in disease

Abstract: Although the following text will focus on magnesium in disease, its role in healthy subjects during physical exercise when used as a supplement to enhance performance is also noteworthy. Low serum magnesium levels are associated with metabolic syndrome, Type 2 diabetes mellitus (T2DM) and hypertension; consequently, some individuals benefit from magnesium supplementation: increasing magnesium consumption appears to prevent high blood pressure, and higher serum magnesium levels are associated with a lower risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
115
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(126 citation statements)
references
References 166 publications
1
115
1
3
Order By: Relevance
“…It has been suggested that magnesium regulates cellular glucose metabolism directly because it serves as an important cofactor for various enzymes and acts as a second messenger for insulin [36] . It was also observed that insulin enhances intracellular magnesium uptake and this in turn mediates diverse effects ascribed to insulin [37] . Furthermore, hypomagnesaemia may induce altered cellular glucose transport, reduced pancreatic insulin secretion, defective post-receptor insulin signalling and/or altered insulininsulin receptor interactions and thus aggravate insulin resistance [38] .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It has been suggested that magnesium regulates cellular glucose metabolism directly because it serves as an important cofactor for various enzymes and acts as a second messenger for insulin [36] . It was also observed that insulin enhances intracellular magnesium uptake and this in turn mediates diverse effects ascribed to insulin [37] . Furthermore, hypomagnesaemia may induce altered cellular glucose transport, reduced pancreatic insulin secretion, defective post-receptor insulin signalling and/or altered insulininsulin receptor interactions and thus aggravate insulin resistance [38] .…”
Section: Discussionmentioning
confidence: 98%
“…Hypertension and its complications may also be the final consequences of increased calcium influx and contraction of VSMC [1,51] . Moreover, it was observed that magnesium acts on most types of calcium channels in VSMC exerting substantial arterial blood pressure-lowering properties, resulting in a reduction of peripheral and cerebral vascular resistance [37,52] . In vivo and in vitro studies in animals (pregnant rats) have demonstrated magnesium-induced relaxation of smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The consequences of low magnesium may lead to a reduction in cerebral blood flow, cerebral vasospasm and increase in neuronal burst. 14,20 Macdonald et al have shown experimentally that magnesium has a vasoprotective effect. 21 This explains the use of magnesium sulphate as a neuroprotectant and antivasospastic agent.…”
Section: Discussionmentioning
confidence: 99%
“…Conditions such as Type 2 Diabetes [10][11][12], Alzheimer's [13,14] and cardiovascular disease [15,16] have been linked with magnesium deficiency, however the mechanisms of Mg 2+ regulation in such disease states are poorly understood [17,18]. Fluorescent chemosensors, in combination with specialised imaging technologies, provide a useful tool to study the role of metal ions in cellular processes as they enable detection in and around cells with spatial and temporal resolution [19].…”
Section: Introductionmentioning
confidence: 99%